Distinct Roles of Glutamine Metabolism in Benign and Malignant Cartilage Tumors With IDH Mutations. (22nd March 2022) - Zhang, Hongyuan; Puviindran, Vijitha; Nadesan, Puviindran; Ding, Xiruo; Shen, Leyao; Tang, Yuning J; Tsushima, Hidetoshi; Yahara, Yasuhito; Ban, Ga I; Zhang, Guo‐Fang; Karner, Courtney M; Alman, Benjamin A.
ABSTRACT: Enchondromas and chondrosarcomas are common cartilage neoplasms that are either benign or malignant, respectively. The majority of these tumors harbor mutations in either IDH1 or IDH2 . Glutamine metabolism has been implicated as a critical regulator of tumors with IDH mutations. Using genetic and pharmacological approaches, we demonstrated that glutaminase‐mediated glutamine metabolism played distinct roles in enchondromas and chondrosarcomas with IDH1 or IDH2 mutations. Glutamine affected cell differentiation and viability in these tumors differently through different downstream metabolites. During murine enchondroma‐like lesion development, glutamine‐derived α‐ketoglutarate promoted hypertrophic chondrocyte differentiation and regulated chondrocyte proliferation. Deletion of glutaminase in chondrocytes with Idh1 mutation increased the number and size of enchondroma‐like lesions. In contrast, pharmacological inhibition of glutaminase in chondrosarcoma xenografts reduced overall tumor burden partially because glutamine‐derived non‐essential amino acids played an important role in preventing cell apoptosis. This study demonstrates that glutamine metabolism plays different roles in tumor initiation and cancer maintenance. Supplementation of α‐ketoglutarate and inhibiting GLS may provide a therapeutic approach to suppress enchondroma and chondrosarcoma tumor growth, respectively. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).